Bibliometric Analysis of Women Leadership in Islam - Loso Judijanto; Hayu Lusianawati (Westscience Press, 2026)
Women leadership in Islam has become an increasingly discussed research topic due to growing academic interest in gender roles, religious interpretation, empowerment, and women's participation in social and institutional contexts. However, existing studies remain fragmented across various disciplines, making it necessary to understand the overall intellectual structure and development of this research field. This study aims to examine the global research landscape of women leadership in Islam through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to women leadership and Islamic perspectives. The collected publications were analyzed using bibliometric techniques, including publication trend analysis, citation analysis, co-authorship analysis, institutional and country collaboration analysis, keyword co-occurrence analysis, overlay visualization, and density visualization through VOSviewer. The findings indicate that research on women leadership in Islam has developed through interdisciplinary contributions involving Islamic studies, gender studies, leadership, sociology, and social development. Influential literature highlights themes related to Islamic authority, gender equality, women's empowerment, and leadership experiences within Muslim societies. The collaboration analysis demonstrates strong international research networks involving institutions and countries from different regions, reflecting the global nature of this academic discourse. Furthermore, keyword analysis reveals that Islam, women, and leadership represent the dominant research themes, while emerging discussions increasingly focus on feminism, patriarchy, gender equality, and Muslim women's participation. This study contributes by mapping the intellectual evolution of women leadership research in Islamic contexts and identifying future research directions related to inclusive leadership models, gender equity, and the role of Islamic values in shaping contemporary women's leadership practice.